HUBUNGAN KUALITAS TIDUR DENGAN KONSENTRASI BELAJAR PADA SISWA DI SMA N 6 PEKANBARU - Ade Febriani; Ganesya Silvia Putri; Nengsi Fitri (JOMIS (Journal of Midwifery Science), 2025)
The American Academy of Pediatrics stated in America that school-age adolescents really need quality sleep and sufficient sleep. Quality sleep and sufficient sleep can reduce various negative problems such as health problems, accidents, problems with decreased concentration and memory and a person's mental health. Students' sleep patterns are correlated with learning concentration. This skill is comparable to student behavior and can be seen through its changes. One important factor that influences the learning process is learning focus. Students' cognition, affective, psychomotor, and science processes are influenced by increased learning concentration. Students with high learning concentration find it easier to understand learning materials. Type of quantitative research using a cross-sectional approach. The measuring instruments used are the PSQI questionnaire and the learning concentration questionnaire, The sampling technique used in this study is purposive sampling. The data collection technique in this study used a questionnaire and also a grid test. The purpose of this study is to determine the relationship between sleep patterns and student learning concentration at SMS N 6 Pekanbaru. shows that the p-value is 0.001 is smaller than 0.05 (p-value <0.05). So it can be concluded that there is a relationship between sleep patterns and student learning concentration at SMA N 6 Pekanbaru. Adequate sleep according to the amount of need is important for health, so that the mind and body feel fresh and ready for activities when they wake up. Everyone has a different optimal amount of sleep depending on their age.